De aluno a professor: a experiência de um professor estagiário nos primeiros passos de docência em Educação Física - Leonardo Miguel Rodrigues Barateiro (2024)
This report, entitled "From student to teacher: The experience of a trainee teacher in the first steps of teaching Physical Education" was carried out as part of the Professional Practicum, a Curricular Unit which is part of the 2nd Cycle of studies to obtain a Master's degree in Teaching Physical Education in Primary and Secondary Schools. The Report is the result of the practicum experience lived in the context of the first contact with the teaching profession in the school subject of Physical Education. The internship occurred at the Ermesinde Secondary School, with concrete action in a resident twelfth-grade class of the Scientific-Humanistic Visual Arts course. The report is written with the aim of discussing the practices, challenges and reflections on the learning that took place during the first steps in teaching during the 2023/24 school year in the context of Supervised Teaching Practice. The document has been subdivided into ten chapters, which describe the experiences throughout the school year, recreating all the work carried out in the first experience as a Physical Education teacher. All the difficulties and experiences that made it possible to transform a student into a teacher are recounted, as are the lessons learned and the strategies used. The document has been written in a chronological sequence, so that when you read it, you can see the whole experience, from the student who starts an internship to the teacher who finishes it. It begins with a brief autobiographical presentation, which moves on to the justification of Physical Education before presenting the contexts in which the professional internship took place, as well as the way the planning was thought out and the baggage I brought with me, which formed the basis for the first steps of the whole process that was configured at the beginning of my profession, as well as the consequent evolution and deepening of emerging themes. KEYWORDS: